Heterostructure plasticized magnesium-based composite material as well as preparation method and application thereof
By introducing heterostructure and multi-scale particle distribution into magnesium-based composite materials, combined with ball milling and vacuum hot pressing processes, the dispersion and embrittlement problems of nano reinforcement bodies are solved, significantly improving the plasticity and strength of the material, and expanding its application scope.
Patent Information
- Application Number
- CN202411250532.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
Nano-reinforced bodies are difficult to disperse in magnesium-based composite materials, resulting in strong plastic inversion, limiting the application range of materials, and traditional preparation methods are difficult to break the embrittlement of composite materials.
AZ61 magnesium alloy powder is mixed with pure titanium carbide and stearic acid by combining low-speed and high-speed ball milling to carry out vacuum hot pressing and hot extrusion processes with gradient heating to form a heterostructure-plastic magnesium-based composite material, including nanometers The reinforcement particle TiC is combined with the second phase of the self-generated micron β-Mg17Al12.
It significantly improves the plasticity of magnesium-based composite materials, maintains high strength, reduces the generation of microcracks, prevents oxidation, realizes the preparation of high-density composite materials, and expands the application potential of materials in the industrial field.
Smart Images

Figure CN119114947A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material science, and specifically relates to a heterogeneous structure plasticized magnesium-based composite material, a preparation method and an application thereof. Background Art
[0002] With the increasing demand for energy conservation and emission reduction, the development of lightweight structural materials has received widespread attention. Nano-enhanced magnesium-based composites have the advantages of low density, high specific strength, specific stiffness, and vibration and noise reduction, and have broad application prospects in aerospace, transportation, and national defense.
[0003] Although the addition of nano-reinforcements can maximize the strength of magnesium alloys without significantly losing plasticity. Since nano-reinforcements are difficult to disperse in the metal matrix, the full reinforcement effect of the composite material is affected, and the plasticity of magnesium-based composite materials is often low, which greatly restricts the application of such materials. The traditional idea of preparing metal-based composites is to disperse the reinforcements as evenly as possible, but this idea still makes it difficult to break the common phenomenon of strength-plasticity inversion in composite materials. Therefore, the development of a preparation method for magnesium-based composites with high strength-plasticity synergy is of great practical significance and can greatly expand the application field of magnesium-based materials. Summary of the invention
[0004] In view of the problems and shortcomings of the prior art, the present invention provides a method for preparing a heterogeneous structure plasticized magnesium-based composite material, comprising the following steps:
[0005] S1: AZ61 magnesium alloy powder, pure titanium carbide and stearic acid are mixed, and low-speed and high-speed ball milling is performed to obtain a mixed powder, and the powder is cooled and then filled and cold pressed;
[0006] S2: The powder after cold pressing in S1 is subjected to a vacuum hot pressing process with gradient temperature increase and exhaust, and then cooled for thermal deformation to obtain a magnesium-based composite material with heterogeneous structure plasticization.
[0007] Furthermore, the mass ratio of pure titanium carbide and stearic acid described in S1 is 0.53-1.18:1.
[0008] Furthermore, the mass percentage of pure titanium carbide in S1 is 0.8-1.3wt.%, the mass percentage of stearic acid is 1.1-1.5wt.%, and the remainder is AZ61 magnesium alloy.
[0009] Furthermore, the low-speed ball milling time described in S1 is 20 hours, the high-speed ball milling time is 1 hour, the low-speed ball milling speed is 100-200 rpm, the high-speed ball milling speed is 280-320 rpm, and the low-speed ball milling is paused for 5 minutes every 15 minutes, the ball milling jar needs to be taken out and hand-cranked every 45 minutes, and the high-speed ball milling process is paused for 5 minutes every 10 minutes.
[0010] Furthermore, the pressure in the cold pressing process described in S1 is set to 2.5 MPa.
[0011] Furthermore, the vacuum hot pressing process described in S2 includes first raising the temperature to 300°C and maintaining it at this temperature for 15 minutes, then raising the temperature to 450°C and maintaining it at this temperature for 15 minutes, and then further raising the temperature to 475°C for exhaust and maintaining it for 30 minutes. After the exhaust is completed, the temperature is kept at 520°C for 1 hour while applying a pressure of 50 MPa.
[0012] Furthermore, the thermal deformation process described in S2 adopts hot extrusion, the extrusion temperature is set to 300-350°C, the extrusion ratio is 15-20:1, and the extrusion speed is 2.5-3.5 mm / s.
[0013] A magnesium-based composite material with a heterogeneous structure plasticization, wherein the magnesium-based composite material has a heterogeneous structure feature, and the magnesium-based composite material further comprises an externally added nano-reinforcement particle TiC and a self-generated micronized β-Mg 17 Al 12 Second phase.
[0014] The invention discloses an application of a heterogeneous structure plasticized magnesium-based composite material, wherein the magnesium-based composite material is applied in the preparation of aerospace materials.
[0015] Technical Effects
[0016] (1) The magnesium-based composite material with a heterogeneous structure plasticized by the present invention can nearly double the plasticity while maintaining the high strength characteristics of the traditional magnesium-based material, compared with the traditional uniform fine-grained magnesium-based composite material. This is crucial for improving the application performance of the material in complex environments. In terms of performance, the compression strength of the magnesium-based composite material with a heterogeneous structure reaches 419±6MPa, and the true strain is as high as 7.3±0.2%. Microcracks are prone to occur in the composite material during processing, especially when the content of reinforcement particles is high. The present invention effectively solves this problem by introducing a heterogeneous structure. The introduction of the heterogeneous structure not only maintains the high strength of the material, but also significantly improves the plasticity, making the composite material easier to form during processing and reducing the generation of microcracks, thereby providing practical value for the wide application of composite materials.
[0017] (2) Through the preparation method of a heterogeneous structure plasticized magnesium-based composite material provided by the present invention, the oxidation phenomenon of the magnesium-based composite material can be prevented by vacuum hot pressing, thereby preventing the composite material from becoming brittle. This method can achieve simultaneous heating and pressurization, which is beneficial to the compactness of powder metallurgy materials, especially for composite materials. In addition, the hot pressing process can achieve the preparation of high-density composite materials with relatively low pressure. This is because, on the one hand, the vacuum environment reduces the participation of gas, making the compaction of powder easier to achieve. On the other hand, under the action of thermal activation effect and pressure, heating can increase the thermal energy of powder particles, improve their diffusion rate and plastic deformation ability, thereby promoting the combination and diffusion of powder particles under lower pressure.
[0018] (3) Through the preparation method of a heterogeneous structure plasticized magnesium-based composite material provided by the present invention, the vacuum hot pressing method allows the size of the bimodal grains to be finely controlled, which directly affects the density and performance of the material. By precisely controlling the grain size, the composite material of the present invention achieves a significant improvement in plasticity while maintaining high strength, which is of great significance for improving the overall performance and processability of the material. The thermal deformation step of the present invention cleverly utilizes the multi-scale particle distribution characteristics of the material, and through precise process control, achieves fine control of the double heterogeneous structure. This step is not only extremely simple in operation, but also easy to implement, providing a solid technical foundation for the industrial production of materials.
[0019] (4) Through the application of a heterogeneous structure plasticized magnesium-based composite material provided by the present invention, the performance of the material obtained by the preparation method is enhanced, thereby expanding the potential for application of magnesium-based composite materials in the industrial field. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0021] Figure 1 EBSD map of the AZ61-TiC magnesium-based composite material of the present invention and the corresponding geometric necessary dislocation density distribution map;
[0022] Figure 2 The SEM image of the heterogeneous magnesium-based composite material AZ61-TiC of the present invention and the corresponding EDS surface scan images of different elements.
[0023] Figure 3The compressive mechanical properties curve of heterogeneous and homogeneous magnesium-based composites AZ61-TiC. DETAILED DESCRIPTION
[0024] The following will be combined with Example 1 of the present invention and the attached Figures 1 to 3 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] S1: Mix magnesium alloy powder AZ61 (purity greater than 99.9%), titanium carbide TiC (purity greater than 98%), and 1.3wt.% stearic acid, and then perform low-speed ball milling for 20 hours and then high-speed ball milling for 1 hour, wherein the low-speed ball milling is paused for 5 minutes every 15 minutes, and the ball milling jar needs to be taken out and hand-cranked every 45 minutes to prevent it from sticking to the wall or agglomeration; during the high-speed ball milling process, it is necessary to pause for 5 minutes every 10 minutes to prevent overheating, and take it out and hand-crank it to obtain a mixed powder; after the ball milling is completed, the powder is placed in a vacuum glove box and cooled, and the powder is taken out of the vacuum glove box for powder filling, and it is quickly taken out for cold pressing after manual compaction; the mold is placed on a 200-ton vertical hydraulic press for cold pressing, and the main cylinder pressure is set to 2.5MPa. Once the set pressure is reached during the downward pressing process, the pressure is maintained for 5 minutes. After the pressure holding time is over, the pressure of the hydraulic press is slowly released to avoid damage to the material or mold due to excessive pressure release;
[0027] S2: The cold-pressed mold was placed in a vacuum hot-pressing furnace for hot-pressing, and vented at 475°C for 30 minutes. After venting, it was kept at 520°C for 1 hour while applying a pressure of 50MPa, and then cooled in the furnace; the material treated with vacuum hot-pressing was plastically deformed, the extrusion temperature was set to 350°C, the extrusion ratio was 19:1, and the extrusion rod speed was 3.5mm / s; and a magnesium-based composite material with heterogeneous structure plasticization was obtained.
[0028] The method achieves large plastic deformation of the initial powder by combining long-term low-speed ball milling with high-speed ball milling technology. This process causes almost all powder particles to be pressed into a flat shape, providing sufficient power for the growth of grains during the subsequent sintering process. During the sintering process, the grains in the powder undergo significant growth, forming coarse grains with uniform size.
[0029] The magnesium-based composite material prepared by the present invention has a heterogeneous structural feature, which exists in two aspects. On the one hand, the grain size of the magnesium alloy matrix presents a bimodal distribution, wherein the size of the coarse grain is about 10-15 μm, and the size of the fine grain is about 1-4 μm. On the other hand, the composite material also contains multi-scale particles (added nano-reinforcement particles TiC and self-generated micronized β-Mg 17 Al 12 The second phase) also shows a non-uniform distribution of particles. Specifically, the particles are sparse in the coarse-grained area and enriched in the fine-grained area.
[0030] The components and their mass percentages of the magnesium-based composite material designed above are titanium carbide TiC 0.8-1.3wt.%, stearic acid 1.1-1.5wt.%, and the balance is AZ61 magnesium alloy. In a further optimized solution, the components and their mass percentages are titanium carbide TiC 1wt.%, stearic acid 1.3wt.%, and the balance is AZ61 magnesium alloy.
[0031] After the vacuum hot pressing process, a coarse grain structure is formed in the bulk material, laying the foundation for subsequent thermal deformation; a gradient heating exhaust process is introduced during the vacuum hot pressing process, which first raises the temperature to 300°C and maintains it at this temperature for 15 minutes, then raises the temperature to 450°C, maintains it at this temperature for 15 minutes, and then further raises the temperature to 475°C and maintains it for 30 minutes. When the temperature is kept at a lower temperature, since the temperature has not yet reached the melting point of the magnesium alloy, a liquid phase will not be formed, and the premature occurrence of metallurgical reactions is avoided. The low-temperature insulation at this stage is particularly beneficial for removing air and volatile impurities from the material, and provides a guarantee for the smooth progress of the subsequent metallurgical process. Finally, the temperature is continued to rise to the target temperature of 520°C. At this stage, since the aforementioned exhaust process has effectively removed the gas, the tiny pores between the powder particles begin to be filled with molten metal, which promotes the metallurgical bonding of the powder particles. Compared with directly heating to the target temperature, the gradient heating exhaust technology adopted by the present invention is more conducive to ensuring the high density and uniformity of the material.
[0032] The thermal deformation step is to plastically deform the block material that has been treated with vacuum hot pressing through a precisely controlled hot extrusion or hot rolling process to achieve a dual heterogeneous structure of the magnesium-based composite material, wherein the setting of the parameters in Example 1 is based on a deep understanding of the material properties and deformation mechanism to ensure that the material can achieve the target heterogeneous structure during the thermal deformation process. Thermal deformation is the key to forming a special structure. In this process, the effect of multi-scale particles superimposed by appropriate thermal deformation can allow part of the material to undergo dynamic recrystallization while part of the material does not undergo dynamic recrystallization, thereby forming a dual heterogeneous composite material. Dual heterogeneity refers to a composite material in which, on the one hand, the matrix presents a bimodal grain structure distribution at the grain scale, and on the other hand, the multi-scale particles also present an uneven distribution. In particular, the added nanoparticles and micron second phase are enriched in the fine grain area and sparse in the coarse grain area. The added nano-TiC particles are enriched in certain areas but are evenly distributed in the area. Their presence also promotes the β-Mg 17 Al 12 phase nucleation, these micronized β-Mg 17 Al 12 The phase promotes dynamic recrystallization during thermal deformation, and a large number of nano-TiC particles can also play a role in pinning the grains, thus eventually forming a fine-grained area with particle enrichment, which further enhances the strength and stability of the material. 17 Al 12 The phase is also rare. Due to the lack of excited nucleation of the second phase particles, dynamic recrystallization is relatively difficult to carry out. Only when the dislocations accumulate to a certain amount can the threshold of dynamic recrystallization be reached. In addition, due to the lack of pinning of nanoparticles, the grains in this area are easy to grow, and finally form a coarse-grained area with sparse particles. This dual isomerization characteristic formed by the thermal deformation process gives the magnesium-based composite material excellent comprehensive performance.
[0033] Combination Figure 1 The microstructure of the extruded magnesium-based composite AZ61-TiC observed by electron backscatter diffraction (EBSD) technology reveals its unique bimodal structural grain characteristics. Among them, the average size of the coarse grains is about 10-15μm, while the average size of the fine grains is about 1-4μm. Figure 1 (a). In particular, Figure 1(b) shows that there are a large number of geometrically necessary dislocations (GND) and even substructures in the coarse grains. In contrast, the GND density in the fine grain area is low. This phenomenon can be attributed to the fact that the coarse grains formed during the sintering process accumulate a large amount of GND after hot extrusion. When the GND accumulates to a certain extent, the dislocations are rearranged to form substructures. The substructures continuously absorb dislocations and evolve into high-angle grain boundaries, thus forming fine grains. Therefore, the fine grains are new grains that have undergone dynamic recrystallization, and the GND density in the fine grain area is low. The coarse grain area shows a high density of GND because of the insufficient dynamic recrystallization during the thermal deformation process, which leads to the residual of a large number of dislocations.
[0034] Figure 2 The secondary electron scanning image of the magnesium-based composite material AZ61-TiC is shown. Figure 2 a is the SEM image of the heterogeneous magnesium-based composite material AZ61-TiC. Figure 2 b is the EDS surface scan corresponding to different elements, Figure 2 c~2f are EDS scans of Mg, Al, Ti, and C respectively. Figure 2 a clearly reveals that most of the second phase is distributed at the grain boundaries, and its corresponding surface scan further confirms that the particle-enriched area is rich in TiC particles, such as Figure 2 b. These second phases and nanoparticles in the fine-grained region play a role of dispersion strengthening, enhancing the microstructural stability of the material. In addition, the synergistic effect of the fine-grained strengthening mechanism significantly improves the strength of the fine-grained region, thereby greatly improving the overall strength of the composite material.
[0035] Figure 3 The compressive mechanical properties of heterogeneous and homogeneous magnesium-based composites AZ61-TiC were compared. The true strain of the homogeneous magnesium-based composite material is 3.8±0.1%, while the true strain of the heterogeneous structure magnesium-based composite material of the present invention is significantly increased to 7.3±0.2%, which is about 92% higher than the homogeneous structure. This significant improvement confirms that the introduction of heterogeneous structure can greatly enhance the plasticity of the material. Although the compressive strength of the heterogeneous structure magnesium-based composite material is 419±6MPa, which is 37±10MPa lower than the strength of the homogeneous composite material, it has only decreased by 8%. This shows that the composite material of the present invention significantly improves plasticity while maintaining a high strength, achieving an excellent balance between strength and plasticity.
[0036] The present invention provides a magnesium-based composite material with a heterogeneous structure plasticized. The coarse-grained region of the magnesium-based composite material has a high-density dislocation, so it can also provide strength, and on the basis of maintaining the high-strength characteristics of traditional magnesium-based materials, the plasticity is significantly enhanced. The introduction of the heterogeneous structure makes the composite material easier to form during processing, reducing the generation of microcracks. The magnesium-based composite material of the present invention contains heterogeneous structural characteristics, which exist in two aspects. On the one hand, the grain size of the magnesium alloy matrix presents a bimodal distribution, wherein the size of the coarse grains is about 10 to 15 μm, and the size of the fine grains is about 1 to 4 μm. On the other hand, the composite material also contains multi-scale particles (added nano-reinforcement particles TiC and self-generated micron β-Mg 17 Al 12 The second phase) also shows a non-uniform distribution of particles. Specifically, the particles are sparse in the coarse-grained area and enriched in the fine-grained area.
[0037] The invention provides a method for preparing a heterogeneous structure plasticized magnesium-based composite material, which has a double heterogeneous structure through ball milling, vacuum hot pressing, hot extrusion, and regulating the microstructure by adjusting the hot extrusion speed, so that the composite material obtains higher strain hardening and excellent passivation crack performance, while maintaining the high strength of the alloy and also improving its toughness and plasticity.
[0038] The invention provides an application of a heterogeneous structure plasticized magnesium-based composite material. Through the preparation method and structure, the application potential of the magnesium-based composite material in the industrial field is broadened, providing practical value for the wide application of the composite material.
Claims
1. A method for preparing a heterogeneous structure plasticized magnesium-based composite material, characterized in that: The following steps are involved: S1: AZ61 magnesium alloy powder, pure titanium carbide and stearic acid are mixed, and low-speed and high-speed ball milling is performed to obtain a mixed powder, and the powder is cooled and then filled and cold pressed; S2: The powder after cold pressing in S1 is subjected to a vacuum hot pressing process with gradient temperature increase and exhaust, and then cooled for thermal deformation to obtain a magnesium-based composite material with heterogeneous structure plasticization.
2. The method for preparing a heterogeneous structure plasticized magnesium-based composite material according to claim 1, characterized in that: The mass ratio of pure titanium carbide and stearic acid described in S1 is 0.53-1.18:
1.
3. The method for preparing a heterogeneous structure plasticized magnesium-based composite material according to claim 1, characterized in that: The mass percentage of pure titanium carbide in S1 is 0.8-1.3wt.%, the mass percentage of stearic acid is 1.1-1.5wt.%, and the remainder is AZ61 magnesium alloy powder.
4. The method for preparing a heterogeneous structure plasticized magnesium-based composite material according to claim 1, characterized in that: The low-speed ball milling time described in S1 is 20 hours, the high-speed ball milling time is 1 hour, the low-speed ball milling speed is 100-200rpm, the high-speed ball milling speed is 280-320rpm, and the low-speed ball milling is paused for 5 minutes every 15 minutes, the ball milling jar needs to be taken out and hand-cranked every 45 minutes, and the high-speed ball milling process is paused for 5 minutes every 10 minutes.
5. The method for preparing a heterogeneous structure plasticized magnesium-based composite material according to claim 1, characterized in that: The pressure during the cold pressing process described in S1 was set to 2.5 MPa.
6. The method for preparing a heterogeneous structure plasticized magnesium-based composite material according to claim 1, characterized in that: The vacuum hot pressing process described in S2 includes first raising the temperature to 300°C and maintaining it at this temperature for 15 minutes, then raising the temperature to 450°C and maintaining it at this temperature for 15 minutes, and then further raising the temperature to 475°C for exhaust and maintaining it for 30 minutes. After the exhaust is completed, the temperature is maintained at 520°C for 1 hour while applying a pressure of 50 MPa.
7. The method for preparing a heterogeneous structure plasticized magnesium-based composite material according to claim 1, characterized in that: The thermal deformation process described in S2 adopts hot extrusion, the extrusion temperature is set to 300-350°C, the extrusion ratio is 15-20:1, and the extrusion speed is 2.5-3.5 mm / s.
8. A heterogeneous structure plasticized magnesium-based composite material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The magnesium-based composite material is characterized by a heterogeneous structure, and the magnesium-based composite material also contains an external nano-reinforcement particle TiC and a self-generated micron β-Mg 17 Al 12 Second phase.
9. The use of a heterogeneous structure plasticized magnesium-based composite material according to claim 8, characterized in that: The magnesium-based composite material is used in the preparation of aerospace materials.
Citation Information
Patent Citations
Preparation method of fine-grain Mg-based composite material comprising AlN (aluminum nitride) particles
CN104928510A
Method for preparing high-strength and high-toughness magnesium-based nano composite
CN105734329A
Powder metallurgy preparation method for high-strengthening-toughening metal-based composite material
CN108080644A
CrCoNi-Al2O3 nano composite material with heterostructure and preparation method of CrCoNi-Al2O3 nano composite material
CN113403517A
Customized construction method of bimodal structure of high-toughness titanium-based composite material
CN116037931A
Cited By
Nano-phase hybrid reinforced magnesium-based composite material and preparation method thereof
CN120888825A
